2021
DOI: 10.1111/hsc.13328
|View full text |Cite
|
Sign up to set email alerts
|

Social care‐related outcomes in Finland. Construct validity and structural characteristics of the Finnish ASCOT measure with older home care users

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…10 An epidemiological study in Japan found that regardless of the degree and type of functional limitation of LTC recipients, their spouses as informal family caregivers experienced a significantly high risk of psychological distress as well as limitations in social participation. 11 Moreover, a systematic review suggested that caregiving burden was determined more by the characteristics of the caregiver and the provision of caregiving tasks than by the characteristics of care recipients. 12 Therefore, every caregiver needs interventions to address their needs and strains.…”
Section: Introductionmentioning
confidence: 99%
“…10 An epidemiological study in Japan found that regardless of the degree and type of functional limitation of LTC recipients, their spouses as informal family caregivers experienced a significantly high risk of psychological distress as well as limitations in social participation. 11 Moreover, a systematic review suggested that caregiving burden was determined more by the characteristics of the caregiver and the provision of caregiving tasks than by the characteristics of care recipients. 12 Therefore, every caregiver needs interventions to address their needs and strains.…”
Section: Introductionmentioning
confidence: 99%
“…of the measures and psychometric testing of the original English language version or cultural adaptation and translations, authors have made different assumptions about whether the measure is formative 1,2 or reflective 15,16 . In some work, the issue of measurement models has been noted, and an 'agnostic' approach taken to analysis that does not commit to either model 17 .…”
Section: Resultsmentioning
confidence: 99%
“…as a PBM, or not). Inconsistent approaches to psychometric evaluation of the same measure have given rise to discussion of the correct approach to the translation and cross-cultural validity or adaptation of the measures for new contexts or populations [15][16][17] . One way of resolving this question is to establish empirically which measurement model, RMM or FM, most accurately describes the ASCOT and ASCOT-Carer.…”
Section: Introductionmentioning
confidence: 99%
“… 70 , 75 A short completion time of the BWS task as a significant scale factor could suggest that the respondents used a heuristic method to make choices quickly 76 or that they made a reduced effort while engaging in the choice tasks and considering the available alternatives properly. The learning effect has not been explored earlier in BWS studies, except in Nguyen et al 24 In addition to two four-task sequences, we tested other sequential divisions of the choice tasks (e.g., the first two tasks vs. the later six tasks), but they were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“… 22 At this time, the official Finnish translations of the ASCOT are available. 23 The Finnish ASCOT measure has been validated, 24 but its preference weights have not been estimated. Evidence indicates that country-specific differences in sociocultural values, demographic backgrounds, and political and economic systems influence valuations of well-being and QoL.…”
Section: Introductionmentioning
confidence: 99%